2015
DOI: 10.14740/wjon610w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Molecular Markers and Implication for Molecular Targeted Therapies in Nasopharyngeal Carcinoma: An Update in an Era of New Targeted Molecules Development

Abstract: The aim of the study was to evaluate the prognostic significance of molecular biomarkers which could provide information for more accurate prognostication and development of novel therapeutic strategies for nasopharyngeal carcinoma (NPC). NPC is a unique malignant epithelial carcinoma of head and neck region, with an intimate association with the Epstein-Barr virus (EBV). Currently, the prediction of NPC prognosis is mainly based on the clinical TNM staging; however, NPC patients with the same clinical stage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 128 publications
1
24
0
Order By: Relevance
“…Though enhanced susceptibility to radiotherapy and excellent local control can be achieved with advances in radiotherapy and chemotherapy, the effectiveness of these treatments requires further improvements, especially with distant metastasis rates and high local recurrence rates [4]. In fact, 30% ~ 40% of NPC patients will develop distant metastasis within 4 years, and the prognoses become poor upon metastasis [5]. Metastasis, related to poor prognosis and death of cancer, is primarily responsible for the recurrence and initiating metastatic behaviours [6].…”
Section: Introductionmentioning
confidence: 99%
“…Though enhanced susceptibility to radiotherapy and excellent local control can be achieved with advances in radiotherapy and chemotherapy, the effectiveness of these treatments requires further improvements, especially with distant metastasis rates and high local recurrence rates [4]. In fact, 30% ~ 40% of NPC patients will develop distant metastasis within 4 years, and the prognoses become poor upon metastasis [5]. Metastasis, related to poor prognosis and death of cancer, is primarily responsible for the recurrence and initiating metastatic behaviours [6].…”
Section: Introductionmentioning
confidence: 99%
“…The differences were all statistically significant, with the exception of distant metastasis. In multivariate analysis, EGFR extent was the only independent factor that predicted disease relapse, loco-regional failure, and mortality due to cancer (48). The present study hypothesized that treatment insensitivity was the primary reason for this unsatisfied curative effect.…”
Section: Discussionmentioning
confidence: 71%
“…Liu et al demonstrated an increased MMP-9 level as an unfavorable prognostic factor for NPC; patients with elevated MMP-9 level had a significantly shorter overall survival (OS) time and higher MMP-9 level was positively associated with the status of lymph node metastasis and clinical stage (39). Therefore, MMPs inhibitor had become one of molecular targeted therapy in development for treatment of NPC (40). One study had shown zoledronic acid (MMP inhibitor) combined with chemotherapy could improve progression-free survival (PFS) and OS in NPC patients with bone metastases (41).…”
Section: Discussionmentioning
confidence: 99%
“…EMT is also recognized as an important step in the metastasis of malignancies and the level of E-cadherin was negatively correlated with the clinical prognosis in NPC (40, 4345). Nowadays demethylation of E-cadherin gene is considered to be a potential therapeutic strategy for patients with NPC (46).…”
Section: Discussionmentioning
confidence: 99%